The Role of HSP90α in Methamphetamine/Hyperthermia-Induced Necroptosis in Rat Striatal Neurons - Liao, Lv-shuang; Lu, Shuang; Yan, Wei-tao; Wang, Shu-chao; Guo, Li-min; Yang, Yan-di; Huang, Kai; Hu, Xi-min; Zhang, Qi; Yan, Jie; Xiong, Kun (Frontiers in Pharmacology, 2021)
Methamphetamine (METH) is one of the most widely abused synthetic drugs in the world. The users generally present hyperthermia (HT) and psychiatric symptoms. However, the mechanisms involved in METH/HT-induced neurotoxicity remain elusive. Here, we investigated the role of heat shock protein 90 alpha (HSP90α) in METH/HT (39.5℃)-induced necroptosis in rat striatal neurons and an in vivo rat model. METH treatment increased core body temperature and up-regulated LDH activity and the molecular expression of canonical necroptotic factors in the striatum of rats. METH and HT can induce necroptosis in primary cultures of striatal neurons. The expression of HSP90α increased following METH/HT injuries. The specific inhibitor of HSP90α, geldanamycin (GA), and HSP90α shRNA attenuated the METH/HT-induced upregulation of receptor-interacting protein 3 (RIP3), phosphorylated RIP3, mixed lineage kinase domain-like protein (MLKL), and phosphorylated MLKL. The inhibition of HSP90α protected the primary cultures of striatal neurons from METH/HT-induced necroptosis. In conclusion, HSP90α plays an important role in METH-induced neuronal necroptosis and the HSP90α-RIP3 pathway is a promising therapeutic target for METH-induced neurotoxicity in the striatum.